Spatiotemporal perturbations of the plasminogen activation system in a rat model of acute organophosphate intoxication - Thomas J. Blackmon; Jeremy A. MacMahon; Pedro N. Bernardino; Ryan E. Hogans; Mei-Yun Cheng; Joan Vu; Ruth Diana Lee; Naomi H. Saito; Ana Cristina Grodzki; Donald A. Bruun; Heike Wulff; Kevin D. Woolard; et al. (Acta Neuropathologica Communications)
Abstract Neuroinflammation is widely posited to be a key pathogenic mechanism linking acute organophosphate (OP)-induced status epilepticus (SE) to persistent brain injury and abnormal electrical activity that contribute to epilepsy and cognitive impairment. The plasminogen activation system (PAS) promotes neuroinflammation in diverse neurological diseases but whether it is activated following acute OP intoxication has yet to be evaluated. To address this data gap, we characterized the spatiotemporal expression patterns of multiple components of the PAS in a rat model of acute intoxication with the OP, diisopropylfluorophosphate (DFP). Adult male Sprague Dawley rats administered DFP (4 mg/kg, sc), atropine sulfate (2 mg/kg, im) and 2-pralidoxime (25 mg/kg, im) went into SE that persisted for hours. One day after acute DFP-induced SE, plasmin activity and protein concentrations of plasminogen activator inhibitor-1 (PAI-1) in the plasma were increased, though not significantly. In contrast, acute DFP intoxication significantly increased brain levels of PAI-1, tissue-type plasminogen activator (tPA), urokinase plasminogen activator (uPA), and transcripts of TGF-β in a time- and region-dependent manner. In the cortex and hippocampus, quantification of PAI-1, tPA, and uPA by ELISA indicated significantly increased levels at 1 day post-exposure (DPE). PAI-1 and uPA returned to control values by 7 DPE while tPA protein remained elevated at 28 DPE. Immunohistochemistry detected elevated PAI-1 expression in the DFP brain up to 28 DPE. Co-localization of PAI-1 with biomarkers of neurons, microglia, and astrocytes demonstrated that PAI-1 localized predominantly to a subpopulation of astrocytes. Cytologically, PAI-1 localized to astrocytic end feet, but not adjacent neurovascular endothelium. Electron microscopy revealed neuronal metabolic stress and neurodegeneration with disruption of adjacent neurovascular units in the hippocampus post-DFP exposure. These data indicate that acute DFP intoxication altered PAS expression in the brain, with aberrant PAI-1 expression in a subset of reactive astrocyte populations.